O estatuto do anti-herói : estudo da origem e representação, em análise crítica do Satyricon, de Petrônio e Dom Quixote, de Cervantes - Arantes, Aldinéia Cardoso (2008)
The classic concept of the hero, hailing from Greek literature, features an individual well-known for his extraordinary feats. Through the course of time, such 'divine' characters failed to adequate themselves to collective will and the classical hero was consequently downgraded towards a 'problematic hero'. The latter's existence and values lay among issues that he was incapable of expressing with a sharp and strict consciousness. The building of the new heroic focus is an idea born during modern times and it is mainly represented in the novel and in the novel genre. However, Petronius's first century AD Satyricon has already brought forth a hero-character with considerable distance from the classical heroes. He is characterized by individualistic traits, full of vices and defects in opposition to the classic noble hero. Satyricon's hero Encolpius incorporates the character that modern criticism would identify as anti-hero. Similar traits were also pinpointed in the character of Cervantes's Don Quixote. Although chronologically distant, Encolpius proves that the anti-hero has not been created and only justified by the modern literary context. Current discussion tries to answer the issue of the anti-hero's origin and the prototype characteristics by means of a critical and interpretative reading. Current bibliographical analysis is theoretically foregrounded on the concepts of the hero by Köthe, Campbell and Feijó. Ideas on the anti-hero by Brombert, González, Lukács and others were analyzed to contribute, within an academic context, towards current research on the subject.